2017
DOI: 10.33012/2017.15184
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Testing of OSNMA for Galileo

Abstract: (UAB) and head of the Signal Processing for Navigation and Communications (SPCOMNAV) group. Previoulsy, he was staff member at the Radionavigation Section in ESTEC/ESA, and involved in the Galileo project and in the development of GNSS receivers and applications. Eckart Göhler received his Diploma in physics from the University Tübingen and his Ph.D. from the Institute for Astronomy and Astrophysics, Tübingen. He worked as a lead software engineer at IFEN GmbH in the receiver technology department. Today he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…In the implementation of OSNMA, Margaria et al (2016) demonstrated the OSNMA in both a commercial GPS receiver and a modified software receiver. Sarto et al (2017) reported the implementation and testing progress of OSNMA for Galileo till 2017. Motella et al (2020) proposed a real-time OSNMA-ready software receiver that includes a detailed set-up and running demonstration.…”
Section: Open Service Navigation Message Authentication For Galileomentioning
confidence: 99%
“…In the implementation of OSNMA, Margaria et al (2016) demonstrated the OSNMA in both a commercial GPS receiver and a modified software receiver. Sarto et al (2017) reported the implementation and testing progress of OSNMA for Galileo till 2017. Motella et al (2020) proposed a real-time OSNMA-ready software receiver that includes a detailed set-up and running demonstration.…”
Section: Open Service Navigation Message Authentication For Galileomentioning
confidence: 99%
“…The performance of the proposed RFC-SPA scheme is compared with the Chimera in GPS [13] and OSNMA in Galileo [17], which are two mainstream authentication schemes under construction for the implementation. The performance of these two schemes has been assessed in the previous works [13,27,28]. The results of these previous assessments are regarded as the performance of the Chimera and the OSNMA.…”
Section: Performance Analysismentioning
confidence: 99%
“…The expected number of starting points to be checked before finding a good key is inversely proportional to p, i.e., 1/p. Given ̂ the hashing time in seconds by the adversary, it takes ℓ ̂ seconds to generate a chain of ℓ keys, and it is expected to take 2 ℓ + 1 ℓ ̂= 2  ̂ℓ ℓ + 1 (12) seconds to test enough starting points to find a spoofed chain of length ℓ. Note that when ℓ = 1, then ℓ/(ℓ+1) = 0.5, and when ℓ is large enough ℓ/(ℓ + 1)  1.…”
Section: E the Online Attackmentioning
confidence: 99%
“…For example, the popular GPS L1 C/A transmits every bit over a period of 20ms, resulting in a throughput of 50-bit/second; for Galileo E1 these numbers are respectively 4ms and 250-symbols/second, encoding bits with a ½ coding rate. The academic literature contains a plenitude of proposals for radionavigation authentication protocols [7] [8] [9] [10] [11] [12]. The standard approach is to adopt and adapt cryptographic protocols from other domains, e.g., network communications.…”
Section: Introductionmentioning
confidence: 99%